IMPLANT-BASED REHABILITATION STRATEGIES FOR THE SEVERELY ATROPHIC MAXILLA - Corina Roxana Cîmpean; Alina Ormenișan; Alexandru Burcea; Claudia Florina Bogdan-Andreescu; Andreea Mariana Bănățeanu; Cristian-Viorel Poalelungi; Laura Nan; Ionuţ Vlad Şerbanică (Romanian Journal of Oral Rehabilitation)
The posterior atrophic maxilla remains one of the most challenging regions in implant dentistry, primarily due to limited residual bone height, compromised bone quality, and maxillary sinus pneumatization. Available treatment options are sinus augmentation procedures, short and ultra-short implants, tilted implants, zygomatic and pterygoid implants, and various bone augmentation techniques. Each approach offers distinct advantages and limitations, and the optimal treatment plan often involves a combination of these methods adapted to the patient's specific anatomical conditions and clinical needs. A wide range of implant solutions is now available to address the complexities of the severely atrophic maxilla. The appropriate implant type and surgical technique selection should consider individual anatomical variations, systemic health status, and prosthetic requirements. This paper presents a case series illustrating different surgical approaches to the severely atrophic maxilla. Additionally, we provide an overview of current implant solutions, with particular attention to their clinical indications, expected outcomes, and inherent limitations.